A calcified chronic total occlusion preclinical model. Issue 3 (3rd April 2020) - Osherov, Azriel B.; Qiang, Beiping; Butany, Jagdish; Wright, Graham A.; Strauss, Bradley H.
Abstract: Objective: To create an experimental chronic total occlusion (CTO) model with calcification by dietary modification (cholesterol, calcium carbonate, vitamin D) and local injection of pro‐calcification factors (dipotassium phosphate, calcium chloride, and bone morphogenetic protein‐2 [BMP‐2]). Background: Percutaneous revascularization of CTOs frequently fails in heavily calcified occlusions. Development of novel approaches requires a reproducible preclinical model of calcified CTO. Methods: CTOs were created in 18 femoral arteries of 9 New Zealand White rabbits using the thrombin injection model. Dietary interventions included a high cholesterol diet (0.5% or 0.25%), calcium carbonate (150 mg × 3–5 days/week), and vitamin D (50, 000 U × 3–5 days/week). In selected animals, BMP‐2 (1–4 μg), dipotassium phosphate, and calcium chloride were injected locally at the time of CTO creation. Animals were sacrificed at 2 weeks ( n = 4 arteries), 6 weeks ( n = 4 arteries), and 10–12 weeks ( n = 14 arteries). Results: CTOs showed evidence of chronic lipid feeding (foam cells) and chronic inflammation (intimal/medial fibrosis and microvessels, inflammatory cells, internal elastic lamina disruption). In calcium/vitamin D supplemented rabbits, mineralization (calcification and/or ossification) was evident as early as 2 weeks post CTO creation, and in 78% of the overall arteries. Mineralization changes were not present in the absence of calcium/vitamin D dietary supplements. Mineralization occurred in 85% of BMP‐treated arteries and 60% of arteries without BMP. Conclusions: Complex mineralization occurs in preclinical CTO models with dietary supplementation of cholesterol with vitamin D and calcium.